Influência marinha na Amazônia Ocidental durante o Mioceno superior - Espinosa, Bruno Scudeiro (2021)
The dynamic environments of western Amazonia during the Neogene included continental-scale wetlands that were episodically influenced by marine incursions originating from the Caribbean. The nature and frequency of such events is highly debated, with a general consensus on short events during the early and middle Miocene. However, scattered evidence for more events up until the late Miocene exists. Based on a palynological analysis of borehole 1AS-9-AM from the Solimões Formation (western Amazonia, Brazil), this provides further support for late Miocene marine influence in the region. Comparisons with other sites in the Solimões Basin indicate an age of earliest Tortonian for an assemblage with foraminiferal linings, acritarchs and dinocysts, totalling ~17.3% of the palynological count (n=374 palynomorphs) at 34 m of depth. This is the topmost sample with a significant amount of marine indicators and its age is consistent even when different biostratigraphic interpretations are appreciated. The data and comparisons also show that a larger proportion of sediments of the Solimões Formation should be placed within the late middle to early late Miocene. The reconstruction of the Solimões deposits in the early Tortonian indicates intermintent low salinity regimes and a persistent connection with the paleo-Orinoco drainage until the closure of this connection in the late Miocene to Pliocene times.